Aspirations and weather shocks: Evidence from rural Zambia - Martin C. Parlasca; Christina A. Martini; Maximilian Köster; Marcela Iba\~nez (Agricultural Economics, 2024)
Aspirations defined as future-oriented desires or ambitions, can determine agricultural investments and rural development. Aspirations are shaped by people's social, cultural, and physical environment and can be affected by external factors such as natural disasters. This article addresses the question of how weather shocks can influence individual and community aspirations. Using primary panel data from two survey rounds before and during a major drought in Zambia, we show that such extreme weather events can be associated with adverse impacts on individual aspirations. Further exploratory analyses suggest that aspirations towards assets that are particularly vulnerable to droughts are affected most. We do not find any significant effects of drought on community aspirations.
Keywords: 330; Africa; climate change; drought; water scarcity